Beef problems on Kansas farms - Poole, G. (My University, 1902)
Introduction: As beef production is one of the most prosperous and promising industries in the state of Kansas, and as it is yet in its infancy of development, there are many problems connected with it which are very necessary for the best success and by many are not thoroughly understood. Of course beef production is a business in which no clean cut rules can be laid down for the feeder to follow in order to make a success, but much is left to the local conditions which I dare say are not the same in any two counties of the state, and also to the judgment of the feeder. It is possible, however, to give a number of the most important considerations on which we may say the minor considerations hinge, as for example, Breed; Best Age to Fatten; Care When Young; Getting on Full Feed; Salt; Water; Shipping, etc. There are many local conditions which effect these but in general I think they remain quite constant over the state. Breeds:--The very first and most important question to be settled and upon which your success as a feeder depends is, “Which Beef Breed is the best for my conditions?” This necessarily demands a complete knowledge of your conditions. It is generally accepted that the best beef breeds for Kansas is the Hereford and Short Horn, each of which have some important points over the other. The Hereford enthusiasts claim the majority of these points, while the Short Horn enthusiasts claim the same. It is necessary then to turn to experiments for our decisions. The Herford cattle have from their earliest history been bred and improved strictly as a beef breed while the Short Horn breeders have been trying to develop a dual purpose breed, therefore we would naturally look to the Herefords to see the highest perfection in beef points.
Citation: Poole, G. Beef problems on Kansas farms. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Beef; Kansas; Livestock; Animal Husbandry; Breeding; Theses